The feasibility and benefits of a 12‐week yoga intervention for pediatric cancer out‐patients. Issue 10 (17th June 2014) - Wurz, Amanda; Chamorro‐Vina, Carolina; Guilcher, Gregory M.T.; Schulte, Fiona; Culos‐Reed, S. Nicole
<x xml:space="preserve">Abstract</x> Background Increasing rates of survival present a new set of psychosocial and physical challenges for children undergoing treatment for cancer. Physical activity (PA) has been shown to be a safe and effective strategy to mitigate the significant burden of cancer and its treatments, with yoga increasingly gaining recognition as a gentle alternative. The purpose of this study was to determine the feasibility and benefits of a 12‐week community‐based yoga intervention on health‐related quality of life (HRQL), select physical fitness outcomes and PA levels (PAL). Procedure Eight pediatric cancer out‐patients (4 male; 4 female; Mage = 11.88, SD = 4.26) participated in the 12‐week intervention consisting of supervised yoga sessions 2 times/week. Participants (patients and parent proxies) completed measures assessing HRQL, physical fitness and PAL at baseline and post‐intervention. Results Rates of recruitment, retention, attendance and adverse events indicated the program was feasible. Wilcoxon Signed Rank tests indicated significant improvements for patient (P = 0.02) and parent reported HRQL (P = 0.03), functional mobility (P = 0.01), hamstring flexibility (left, P = 0.01 and right P = 0.02), and total PAL (P = 0.02) pre to post intervention. Conclusion This 12‐week community‐based yoga intervention was feasible and provides preliminary evidence for the benefits of yoga on HRQL, physical fitness and PAL in pediatric cancer out‐patients. In a population where sedentary behavior and the associated co‐morbidities are a growing concern, these results promote the continued exploration of yoga programming. Pediatr Blood Cancer 2014; 61:1828–1834. © 2014 Wiley Periodicals, Inc.